2021
DOI: 10.55151/ijeedu.v3i2.61
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Implication Problem Posing Learning Model on Students in High Schools

Abstract: Problem posing is a learning model that requires students to compose their questions or solve a problem into more straightforward questions that refer to solving the problem based on the initial situation. The study aimed to determine the increase of students in mastering the learning material through the Problem Prosing Learning Model. The type of research used in this study is quasi-experimental research. The sample used was 64 high school students with mathematics as the learning subject. There are two clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Numerous TAM-based e-learning studies have confirmed the positive effects that PE and PU have on BI while utilizing digital instructional tools (e-learning) [1,2]. PE and PU directly affect students' BI to utilize e-learning, so the more accessible and valuable the platform, the higher the likelihood that students will intend to use it [3].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous TAM-based e-learning studies have confirmed the positive effects that PE and PU have on BI while utilizing digital instructional tools (e-learning) [1,2]. PE and PU directly affect students' BI to utilize e-learning, so the more accessible and valuable the platform, the higher the likelihood that students will intend to use it [3].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This epidemic time can train and instill in kids the habit of being independent learners by participating in various online programs. In addition, students can collaborate to solve learning problems and confront real-world issues [2].…”
Section: Introductionmentioning
confidence: 99%
“…Formal environmental education is an environmental field activity organized through primary, secondary, and higher education schools. It is carried out structured and tiered manner using an integrated curriculum approach or a monolithic (separate) curriculum [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the teacher is an actor who has the ability, motivation, and adequate readiness to carry out teaching and learning tasks in the classroom. Therefore, the implementation of a quality learning process, among others, is primarily determined by the teacher having professional competence according to the demands of the law on teachers and lecturers [2].…”
Section: Introductionmentioning
confidence: 99%